The Influence of Intellectual Capital, Enterprise Risk Management, and Capital Structure on Firm Value - Kholifah, Nining; Eliza, Any; Putri, Rosydalina (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research analyzes the effect of intellectual capital, enterprise risk management, and capital structure on firm value. The population consisted of manufacturing companies listed on the Jakarta Islamic Index (JII) between 2017 and 2021. Purposive sampling was employed to choose the sample, consisting of ten companies. The data was analyzed using multiple linear regression assisted by the SPSS Statistic 25. The findings revealed that partial intellectual capital and capital structure had little effect on firm value. However, enterprise risk management has a considerable beneficial impact on firm value. Intellectual capital, enterprise risk management, and capital structure influence firm value. Implication Research Companies are expected to reassess their resource utilization in the form of physical and non-physical aspects, such as employee training, the use of appropriate technology, and transparency and initiatives regarding risks and how to prevent them from increasing investor confidence in the company's quality. Managers are expected to consider whether to take funds in the form of debt or equity and manage their debt properly. It is hoped that it will be useful as additional reference material for future researchers, allowing them to add or include other variables, use different types of methods, and expand into other company sectors. Future researchers can use other risk management standards, such as ISO 31000, to provide more diverse and accurate results.